Web-oriented Educational System for Supporting Students’ Learning Activity Based on Cognitive Prototypes - Ryzhov Oleksii; Popov Andrii (International Journal of e-Education, e-Business, e-Management and e-Learning, 2014)
This article presents a Web-oriented Educational System (ES) based on prototypes of human cognitive structures (CS) which major goal is stimulation of students’ independent work. The theoretical foundation of the system comes from cognitive science, particularly from the Prototype Theory that declares that there are so-called cognitive structures in the mind - mental representations on which human thinking is based. This work is a step towards externalizing human CSs and decide if it is expedient to leverage their prototypes as a basis around which students’ learning activity on knowledge acquisition should be organized. Earlier, we determined a data structure that was named cognitive prototype (CP) as a natural knowledge pattern referring to human CSs. We have developed a web-based application as an educational environment for CP-based organizing and supporting both teaching and learning processes. Teacher’s module is designed as a tool to assist in describing science objects and concepts in terms of CPs and supervise students’ independent work. The latter is built around training exercises incurring from the data structure of CP. Here are two principled aspects: 1) automatically and randomly generated training exercises for students to be done and 2) the exercises are based on knowledge patterns corresponding to the human CSs, which is going to enhance students’ knowledge digestion.
Keywords: Cognitive structure; knowledge pattern; training exercises; UML-model